Hormonal contraceptive use is associated with reduced central serotonergic activity indexed by the loudness dependence of auditory evoked potentials - Normannseth, Henrik; Hatlestad-Hall, Christoffer; Rygvold, Trine Waage; Hadzic, Alena; Andersson, Stein (Frontiers in Human Neuroscience, 2025)
ObjectiveHormonal contraceptives (HCs) are linked to mood disturbances, but the neurobiological mechanisms remain unclear. This study investigated whether HC use is associated with altered central serotonergic activity, using the loudness dependence of auditory evoked potentials (LDAEP).MethodsFifty-four healthy women (30 current HC users and 24 non-users) completed EEG recordings to assess LDAEP. Depressive symptoms were quantified using the Beck Depression Inventory-II. Between-group analyses were controlled for age and depressive symptoms, and effects of menstrual cycle phase, HC type, and mood-related side effects were also examined.ResultsHC users showed significantly steeper LDAEP slopes than non-users across components (all p ≤ 0.028) consistent with reduced central serotonergic activity. This remained significant controlling for age and depressive symptoms. No significant effects of menstrual cycle phase or HC type, but HC users reporting adverse mood effects had more somatic symptoms, without corresponding LDAEP differences.ConclusionThis study is, to our knowledge, among the first to explicitly test an a priori hypothesis that HC use is associated with reduced serotonergic activity indexed by LDAEP in healthy women, and shows that HC use is linked to attenuated central serotonergic activity independent of mood symptoms. These findings underscore the role of sex hormones in shaping serotonergic function and may explain individual variability in mood and antidepressant response.